2021
DOI: 10.3390/ijerph18041644
|View full text |Cite
|
Sign up to set email alerts
|

Age-Friendly Cities and Communities: State of the Art and Future Perspectives

Abstract: The number of older adults is increasing rapidly, and this demographic shift places an increased level of strain and tension on the various international healthcare and welfare systems [...]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 75 publications
(131 reference statements)
0
18
0
1
Order By: Relevance
“…However, the current design of the city is not conducive to the prevention of falls for the elderly to a certain extent, and has a negative impact on the well-being of the elderly, including the lack of access to daily services, and the buildings cannot provide enough space for the elderly and people with mobility impairments [ 8 ]. One way to solve the issues above and support the elderly to live a satisfied life is to build elderly-friendly cities and communities [ 9 ]. Studies have shown that communities with better street connectivity and daily life services tend to improve physical activities of the elderly [ 10 ], and communities roads with low-lying edges and barrier-free sidewalks will improve the travel independence of the elderly [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the current design of the city is not conducive to the prevention of falls for the elderly to a certain extent, and has a negative impact on the well-being of the elderly, including the lack of access to daily services, and the buildings cannot provide enough space for the elderly and people with mobility impairments [ 8 ]. One way to solve the issues above and support the elderly to live a satisfied life is to build elderly-friendly cities and communities [ 9 ]. Studies have shown that communities with better street connectivity and daily life services tend to improve physical activities of the elderly [ 10 ], and communities roads with low-lying edges and barrier-free sidewalks will improve the travel independence of the elderly [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Higher level education institutions have an enormous role here to ensure that students are best prepared to engage in this infrastructure and plan accordingly. Hoof and Marston (2021) place emphasis on all members of the wider scientific community, local, regional, and national governments along with social enterprises and industry leaders working together can afford citizens various opportunities for active engagement within age-friendly cities and ecosystems. This is an example of excellent community engagement with the development of educational pathways which can be provided by higher level institutions.…”
Section: Community Engagement In Higher Educationmentioning
confidence: 99%
“…In essence, it is the sharing of knowledge, expertise, and skills to make a difference. This is an opportunity for academics, stakeholders, policymakers and governments, and other personnel within industry to ensure that the adjoining facets associated to the quality of life for both younger and older people are met (Hoof & Marston, 2021). All of this can positively benefit wider communities.…”
Section: Community Engagement In Higher Educationmentioning
confidence: 99%
“…In the urban environment, the AFC is gaining more relevance because the elderly population represents a high and growing percentage of the population in society, hence the need to respond adequately to their daily and basic needs. Eight domains should be observed in an AFC: Outdoor Spaces and Buildings; Transportation; Housing; Respect and Inclusion; Social Participation; Civic Participation and Employment; Communication and Information; and Community Support and Health Services [58,59].…”
Section: Age-friendly Citymentioning
confidence: 99%
“…De Oliveira et al ( 2019) found a huge number of references in the scientific literature from 2007 to 2017 about the implantation and evaluation of AFCs in the world and highlighted international concern about age pyramid change and longevity [60]. Rémillard-Boilard et al (2021) compared the experience of eleven cities located in different countries.…”
Section: Age-friendly Citymentioning
confidence: 99%